Efficient energy transfer from Bi3+ to Mn2+ in CaZnOS for WLED application. Issue 32 (29th July 2021) - Yang, Yun-Ling; Yuan, Jia-Yong; Fan, Yu-Ting; Wan, Dong-Yun; Li, Qian-Li; Zhao, Jing-Tai; Zhang, Zhi-Jun
Abstract : The crystal structure of the Bi 3+ and Mn 2+ ion co-doped CaZnOS phosphor and its use in fabricating white LEDs. Abstract : A series of Bi 3+ and Mn 2+ co-doped CaZnOS phosphors with a tunable emission color have been synthesized by a high temperature solid-state reaction method. Their crystal structure, spectroscopic properties, energy transfer and thermal quenching have been investigated systematically. An intense blue-green emission band at 485 nm and a red emission band at 616 nm were observed at an excitation wavelength of 375 nm, owing to the 3 P1, 0 → 1 S0 transition of Bi 3+ and the 4 T1 ( 4 G) → 6 A1 ( 6 S) transition of Mn 2+, respectively. The tunable color from blue-green, white light to red light can be obtained by varying the Mn 2+ ion concentration from 0.005 to 0.015 in CaZnOS:Bi 3+ . The decay time decreased from 642 to 273 ns with the Mn 2+ ion concentration x increasing from 0.005 to 0.015, and the energy transfer efficiency η T can reach up to 65% in the CaZnOS:Bi 3+, 0.015Mn 2+ phosphor. As the temperature increases from 300 to 420 K, the emission intensity is maintained at 67%, and the activation energy E a is estimated to be 0.28 eV. An LED fabricated using CaZnOS:Bi 3+, 0.01Mn 2+ exhibited the chromaticity coordinates and corrected color temperature (CCT) of (0.338, 0.364) and 4655 K, respectively. These results validate the promising applications of the CaZnOS:Bi 3+, Mn 2+ phosphor in UV white LEDs.